2012
DOI: 10.1007/s11136-012-0138-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Brazilian version of Chronic Liver Disease Questionnaire

Abstract: CLDQ-BR was validated in Brazilian population and was appropriate for use in patients with liver disease of different etiologies and degrees of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
13
1
1
Order By: Relevance
“…For the construct validity of the CEQ-Br, a good correlation was identified between the total CEQ-Br score and all SF-36 domains. The SF-36 is widely used for analyzing construct validity in patient-reported health measurement instruments such as the Brazilian Portuguese versions of the Neck/Bournemouth Questionnaire [ 16 ] and the Chronic Liver Disease Questionnaire [ 17 ]. Participants reported that the CEQ-Br was easy to answer, and only 14.3% of women considered it difficult or very difficult to answer.…”
Section: Discussionmentioning
confidence: 99%
“…For the construct validity of the CEQ-Br, a good correlation was identified between the total CEQ-Br score and all SF-36 domains. The SF-36 is widely used for analyzing construct validity in patient-reported health measurement instruments such as the Brazilian Portuguese versions of the Neck/Bournemouth Questionnaire [ 16 ] and the Chronic Liver Disease Questionnaire [ 17 ]. Participants reported that the CEQ-Br was easy to answer, and only 14.3% of women considered it difficult or very difficult to answer.…”
Section: Discussionmentioning
confidence: 99%
“…However, transplantation may be a traumatic and highly stressful experience, among other reasons, because of the risks involved. Among these are death, relapse of the disease and dependency on immunosuppressants which may negatively interfere with the recipient’s quality of life (Grinyó et al, 2012; Pérez-San-Gregorio et al, 2012). Fantasies about the donor, symptoms of anxiety, depression and posttraumatic stress, or rejection of body image are psychological problems that usually appear after transplantation (Pérez-San-Gregorio et al, 2005; Baranyi et al, 2013; Annema et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A particular specific instrument is the Chronic Liver Disease Questionnaire (CLDQ), developed by Younossi et al [8] . It is useful in all etiologies of liver disease at any severity stage [2,3] and appears to provide a valuable measure of HRQoL in CLD across different cultures [2,3,[12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%